A General Model for the Helical Structure of Geophysical Flows in Channel Bends. Issue 23 (11th December 2017) - Azpiroz‐Zabala, M.; Cartigny, M. J. B.; Sumner, E. J.; Clare, M. A.; Talling, P. J.; Parsons, D. R.; Cooper, C.
Abstract: Meandering channels formed by geophysical flows (e.g., rivers and seafloor turbidity currents) include the most extensive sediment transport systems on Earth. Previous measurements from rivers show how helical flow at meander bends plays a key role in sediment transport and deposition. Turbidity currents differ from rivers in both density and velocity profiles. These differences, and the lack of field measurements from turbidity currents, have led to multiple models for their helical flow around bends. Here we present the first measurements of helical flow in submarine turbidity currents. These 10 flows lasted for 1–10 days, were up to 80 m thick, and displayed a consistent helical structure. This structure comprised two vertically stacked cells, with the bottom cell rotating in the opposite direction to helical flow in rivers. Furthermore, we propose a general model that predicts the range of helical flow structures observed in rivers, estuaries, and turbidity currents based on their density stratification. Key Points: First direct measurements of the helical flow structure of turbidity currents shown as they travel around a bend Turbidity currents of different thicknesses and velocities exhibit the same helical flow structure We reconcile current controversy with a new model that explains helical flow structure for a wide range of geophysical flows